The Accelerator as a Generator of Steady Growth - Alexander, Sidney S. (Quarterly Journal of Economics, 1949)
Introduction: The theory of the accelerator to date, 174. — How steady growth is generated, 176. — Influence of the investment period, 180. — Influence of the income period, 181. — A more general case, 182. — Qualifications, 186. — Price as a stabilizer, 188. — Appendix, 193.